Is it all That Bad When Living with an Intracellular Protozoan? The Role of Trypanosoma cruzi Calreticulin in Angiogenesis and Tumor Growth - Ramírez-Toloza, Galia (Front Oncol, 2015)
The immune system protects against disease, but may aberrantly silence immunity against “altered self,” with consequent development of malignancies. Among the components of the endoplasmic reticulum (ER), important in immunity, is calreticulin (CRT) that, in spite of its residence in the ER, can be translocated to the exterior. Trypanosoma cruzi is the agent of Chagas disease, one of the most important global neglected infections, affecting several hundred thousand people. The syndrome, mainly digestive and circulatory, affects only one-third of those infected. The anti-tumor effects of the infection are known for several decades, but advances in the identification of responsible T. cruzi molecules are scarce. We have shown that T. cruzi CRT (TcCRT) better executes the antiangiogenic and anti-tumor effects of mammal CRT and its N-terminus vasostatin. In this regard, recombinant TcCRT (rTcCRT) and/or its N-terminus inhibit angiogenesis in vitro, ex vivo, and in vivo. TcCRT also inhibits the growth of murine adenocarcinomas and melanomas. Finally, rTcCRT fully reproduces the anti-tumor effect of T. cruzi infection in mice. Thus, we hypothesize that, the long reported anti-tumor effect of T. cruzi infection is mediated at least in part by TcCRT.